Volatility risk premium: new insights into the systematic edge in the market for option sellers - Serrano, Alexandre Miguel de António (2021)
Financial options have been at the forefront of financial innovation. Their value depends significantly on volatility, one of the most studied variables of financial markets for a long time. Our study provides empirical evidence on the dynamics of the relationship between realized volatility of asset returns and implied volatility extracted from option prices, and on the so-called "volatility risk premium". We confirm that the volatility risk premium is still present in today’s market. Most literature looks at the volatility risk premium as a tool to investigate other financial dynamics. We innovate by investigating the patterns of volatility risk premium singularly as a time series, and so assess whether this is a stationary series, as well as if it presents signs of quarterly seasonality and/or marginal effects from two explanatory variables. We find a clear indication of stationarity and valuable marginal effects by financial variables such as realized volatilities. We also update the literature on the comparison between indices and individual equities surrounding the volatility risk premium; our results confirm that previous findings of a larger premium in individual equities are still applicable nowadays. Lastly, by analyzing option prices, we empirically confirm that volatility risk premium provides a monetary option mispricing. The results we obtain are supported by daily observations, from 2000 to 2020, on three equity indices, five individual equities, one commodity exchange-traded fund, one currency exchange-traded fund, and one emerging-market exchange-traded fund.